2024
DOI: 10.1021/acs.inorgchem.3c04371
|View full text |Cite
|
Sign up to set email alerts
|

AX·(H2SeO3)n (A = K, Cs; X = Cl, Br; n = 1, 2): A Series of Ionic Cocrystals as Promising UV Birefringent Materials with Large Birefringence and Wide Band Gap

Mengmeng Zhu,
Junbo Wang,
Lei Hou
et al.

Abstract: The design and syntheses of new birefringent crystals will be of great importance in commercial applications and materials science. A series of ultraviolet (UV) birefringent crystals, AX•(H 2 SeO 3 ) n (A = K, Cs; X = Cl, Br; n = 1, 2), with large sizes up to 23 × 6 × 3 mm 3 , was successfully synthesized by simple aqueous solution method. These four compounds belong to three different space groups. Isomorphic KCl•(H 2 SeO 3 ) 2 and CsCl•(H 2 SeO 3 ) 2 crystallize in the P 1 space group, while CsBr•(H 2 SeO 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“… 18 It can be observed that Pb 2 (SeO 3 )(SiF 6 ) exhibits a large birefringence in these selenites, second only to KCl·(H 2 SeO 3 ) 2 (0.17 @ 532 nm). 64 However, Pb 2 (SeO 3 )(SiF 6 ) demonstrates the largest birefringence among the selenites without hydrogen, and it is the sole example of lead selenite with a large birefringence (Δ n ≥ 0.1) and wide bandgap ( E g ≥ 4.2 eV). This result highlights the effectiveness of perfluorinated group modification in achieving dual enhancement of the bandgap and birefringence in selenite systems.…”
Section: Resultsmentioning
confidence: 99%
“… 18 It can be observed that Pb 2 (SeO 3 )(SiF 6 ) exhibits a large birefringence in these selenites, second only to KCl·(H 2 SeO 3 ) 2 (0.17 @ 532 nm). 64 However, Pb 2 (SeO 3 )(SiF 6 ) demonstrates the largest birefringence among the selenites without hydrogen, and it is the sole example of lead selenite with a large birefringence (Δ n ≥ 0.1) and wide bandgap ( E g ≥ 4.2 eV). This result highlights the effectiveness of perfluorinated group modification in achieving dual enhancement of the bandgap and birefringence in selenite systems.…”
Section: Resultsmentioning
confidence: 99%
“…However, the introduction of SCALP often leads to a significant redshift in the cut off edge of compounds. In current research, to ensure the bandgap of compounds, two strategies are commonly employed: (1) Introducing alkali metals and alkaline earth metals without d–d and f–f transitions to prevent the redshift of the cut-off edges of the compounds, 30 such as K 2 Sr 4 (PO 3 ) 10 (6.20 eV), 31 Rb 3 MgB 5 O 10 (6.49 eV), 32 Cs 6 Mg 6 (PO 3 ) 18 (6.52 eV), 33 KBa 2( PO 3 ) 5 (7.43 eV); 34 (2) Introducing halogen ions with high electronegativity, which facilitates a blueshift in the cut-off edge of the compounds, 35 such as Rb 3 Pb 2 (CH 3 COO) 2 Br 5 (3.12 eV), 36 (NH 4 )SbCl 2 (SO 4 ) (4.54 eV), 37 CsBr·(H 2 SeO 3 ) 2 (5.19 eV), 38 KCl·(H 2 SeO 3 ) 2 (5.44 eV), 38 Na 2 B 6 O 9 F 2 (7.33 eV). 39…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is essential to examine artificial crystals’ birefringence in optical functional materials. 3–7 Birefringent crystal materials, a type of linear optical material, are widely used in high-precision scientific research tools, optical communication, and various other scientific and technological disciplines. 8,9 They are also capable of modulating and detecting the polarization state of light.…”
Section: Introductionmentioning
confidence: 99%